Envisioning the Future: Worklife and Counselling - Peavy, R. Vance (Canadian Journal of Counselling and Psychotherapy, 1993)
This analytical essay describes scenarios of what work and personal life may modem-post-industrial society and how societal changes may impact on the lives of people. Based on these futuristic observations, suggestions are offered about how counselling can be revised to prepare counsellors to more adequately meet the needs of clients in post-industrial society. One of the principal recommendations is to infuse counsellor preparation and counselling practice with constructivist concepts including a psychology of the self based on narrativity.